6: How to remove and replace the blower fan of your diesel-powered maize shelling machine - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
A practical guide on how a framer can remove and replace the blower fan in the event that it is broken. A broken fan affects the balance of the machine; and the bearing of the machine. It will not produce quality grain and therefore needs immediate attention. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.